The Relationship of Gadget Use to Social Interaction and Learning Achievement Levels in Sagulung Elementary School Students in Batam City 2023 - Elvira Agnestia Ningrum; Nelli Roza; Regina Natalia (Future Science, 2024)
Gadgets are one part of technological development that always presents the latest technology that can help make human activities easier. The impact of gadgets in the era of globalization has positive and negative impacts The positive impact of using devices is that it can make it easier to find information, including information, and can be used over long distances. Devices can also have negative impacts, such as reduced socialization of children and disrupting the process of child development. Prolonged use of devices limits learning opportunities, thus negatively affecting students' grades and learning outcomes. The purpose of this study was to analyze the relationship between the use of social interaction devices and students' academic achievement at SD Negeri 013 Sagulung, Batam City in 2023. This study included observational analysis with a cross-sectional design, with a total of 64 students. respondents. The sampling technique was stratified random sampling. The research instrument was developed by the researcher based on the theory of variables and statistical tests using the Chi-square test. The results of the chi-square test obtained from 36 students of SD Negeri 013 Sagulung with unrestricted gadget use poor social interaction as many as 23 students (63.9%) with a p-value = 0.047 <0.05, meaning that there is a significant relationship between gadget use and student social interaction. In addition, the results were also obtained from 36 students of SD Negeri 013 Sagulung with unrestricted gadget use with low learning achievement results as many as 24 students (66.6%), with a p-value = 0.027 <0.05, meaning that there is a significant relationship between gadget use and student learning achievement. Schools if they want to improve student learning achievement need to regulate the use of gadgets at school and for parents need to make rules and control children while at home.